COVID-19 Mitigation and Global Justice: On the Swedish Experiment - Jouni Korhonen; Birk Granberg; Outi Korhonen; Juha-Pekka Snäkin (Boffin Access, 2022)
The novel coronavirus (from here on COVID-19) is an example of the many acute threats that the global society is creating to the sustainability of animal, ecosystem and human health as well as to global justice including economically sustainable development. COVID-19 is relatively unknown to natural science. The virus and its mitigation operate at the interface of various scientific disciplines (e.g. medicine), social sciences (e.g. strategic planning) and societal development (e.g. sustainability). COVID-19 also requires diverse stakeholders to take responsibility for the situation, political ideology inspired activism and an effort to achieve a truly global, not only Western solution, to the crisis. The objective of this paper is to argue that the human rights basis and the basic pillars of the “Swedish Experiment’s” approach to COVID-19 mitigation of the pandemic constitute a promising pathway for co-learning in the adaptation to the COVID-19 era. The authors find four pillars in the Swedish Experiment: 1) Natural Science, 2) Social Science, 3) Political Ideology and 4) Their mutually amplifying feed-back loops.